Evaluation of Genetic Diversity of Local and Exotic Tomatoes using Morphological Traits and Simple Sequence Repeat Molecular Markers - Omoyeni, Deborah; Fayeun, Lawrence; Odiyi , Alexander; Mogaji , Babatunde; Adegbaju, Maxwell (Journal of Science, Technology and Innovation Research, 2026)
This study investigated the genetic diversity among local, exotic tomato varieties, and their progenies, recognizing the crop's global importance and the necessity of germplasm knowledge for breeding and conservation. The research employed both morphological traits and simple sequence repeat molecular markers. Morphological data were analyzed using Principal Component Analysis and Single Linkage Cluster Analysis, while molecular data were processed with Numerical Taxonomy and Multivariate Analysis System Software. Results revealed significant genetic diversity among the tomato genotypes. However, inconsistencies were observed in genotype clustering when comparing morphological and molecular characterization, although some genotypes showed consistent grouping across both methods. The study concludes by recommending the combined application of morphological traits and molecular markers for comprehensive diversity studies, leveraging their complementary effects for more robust insights into tomato germplasm.